Retrospective evaluation of children with immune thrombocytopenic purpura and factors contributing to chronicity - Tülin Güngör; Özlem Arman Bilir; Vildan Koşan Çulha; Ali Güngör; Abdurrahman Kara; Fatih Mehmet Azık; Hüsniye Neşe Yaralı (Pediatrics and Neonatology, 2019)
Objective: Immune thrombocytopenic purpura (ITP) is the most common cause of acquired thrombocytopenia children. The aim of this retrospective study is to describe presenting features and clinical characteristics of ITP and evaluate clinical course, treatment modalities, and complications and determine the effects of preceding infection history, age, gender, treatment modality, and admission platelet count on chronicity. Method: Two hundred and eleven patients who were diagnosed ITP and followed-up in Department of Pediatric Hematology, Ankara Children Hematology Oncology Education and Research Hospital between January 2008 and September 2012 were included. Age of the patients, gender, date of admission, date of diagnosis, complaint in the application, previous infection and laboratory tests were recorded. Results: Mean age of the patients on diagnosis was 5.4 ± 4.1 years. The female/male ratio was 1.03. The clinical courses were determined as acute or chronic in 72% and 28% of patients respectively. Mean age at diagnosis was significantly higher in chronic ITP (p < 0.01). Chronic course was significantly higher in female patients (p < 0.05). The most frequent complaint was bruises on the skin (68%). The most common physical examination findings were petechiae, purpura and ecchymosis (89%). Patients with a history of past infection (53.6%) and who had serologically positive infection (15.6%) frequently had acute course (p < 0.01). The most common serologically positive infection was Rubella. The mean platelet count was significantly higher in chronic ITP (p < 0.01). In the initial treatment of patients admitted in the acute phase, megadose methylprednisolone (MDMP) was used in 31% of patients, intravenous immune globulin (IVIG) in 55% of patients and anti-D in 2% of patients while 12% did not receive any treatment. There were no significant differences between the recurrence rate and treatment modality (p > 0.05). Conclusion: In our study, in females and in patients without any history of past infection, platelet count >20 × 109/L and initial diagnosis age > 10 years were found to increase the probability of chronic disease, which is compatible with the literature. Key Words: child, corticosteroid, immune thrombocytopenic purpura, intravenous immune globulin